Task-biased technological change in Germany : Is it the routine or the manual? - Seegers, Marco [Verfasser]; Ehmann, Kathrin [Verfasser] (My University, 2025)
“Technological change in the workplace affects individuals’ tasks and work organisation in different ways. However, research on structural labour market change and jobs at risk of technological substitution often assumes routine-biased technological change (RBTC) rather than examining how different technologies affect tasks. This chapter takes the analysis of RBTC to the workplace level in Germany. We review key contributions to task-based technological change at the labour market, firm, and employee and task levels. Combining the task approach with ideas from the socio-technical systems approach, we present evidence against RBTC in Germany. Propensity score matching models with data from the 2018 German BIBB/BAuA Employment Survey show that the introduction of software complements all types of tasks, while new machines/plants and manufacturing/process technologies replace analytical and interactive non-routine tasks and complement (routine) manual tasks. On the basis of these findings, we dispute that the ‘routine’ category is suitable for inferring risks of technological task substitution at the workplace level. When ‘routine’ is conceptualised as a way of organising work rather than a task content, we show that the introduction of software reduces task standardisation while other technologies increase task standardisation." (Authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.2.1 Technologisierung; 370; 600; Arbeitsmarkt; Arbeitsplatz; Technischer Wandel; Routinetätigkeit; Substitutionseffekte; Software; Manuelle Arbeit